Sample Preparation for Trace Analysis of Iron, Copper and Zinc in Thai Fruit Wines by ICP-AES - Rikan KUNNO; Chalerm RUANGVIRIYACHAI; Saksit CHANTHAI (Walailak Journal of Science and Technology, 2011)
Trace analysis of iron (Fe), copper (Cu) and zinc (Zn) in local Thai fruit wines was conducted by inductively coupled plasma-atomic emission spectrometry (ICP-AES). The sample preparation of the fruit wines prior to analysis by optimized ICP-AES conditions was studied by comparing the de-alcoholization and acid digestion methods using conc. HNO3, conc. H2SO4 and H2O2. It was found that both methods of sample treatment gave slightly different metal contents in the fruit wines, but the ratio of conc. HNO3/H2O2 (10:1, v/v) was preferred, resulting in the contents of Fe, Cu and Zn in the wine samples ranging from 1.3 - 4.8, 0.050 - 1.3 and 0.37 - 3.4 mg/l, respectively. The mean recoveries of these metals were in the range of 97.9 - 101 %. Similar precision with RSDs of < 4.5 % were obtained. The standard curves showed good linearity with a correlation coefficient of > 0.9956. The LOD (3SD) and LOQ (10SD) for the acid digestion method, estimated from the noise on the signal obtained for its blank, were also investigated.